FATORES DETERMINANTES DA MORTALIDADE DE MICRO E PEQUENAS FARMÁCIAS DA BAIXADA SANTISTA: sob o olhar do farmacista - Cunha, Mauricio Ayres (2012)
This work studied the pharmaceutical segment of micro and small pharmacies in the region of Santos, in relation to determinants of mortality in the segment, under the gaze of the owners and managers of pharmacies, since in recent years the segment suffered a shrinkage as well migration of pharmacies micro and small businesses to more peripheral areas of the cities of the region of Santos. The methodology used for the research was qualitative, through an exploratory research and literature, and as an instrument for data collection interviews with semi-structured, applied to managers and owners of seven pharmacies in the region of Santos. Five of them active and two closed in the cities of Santos, São Vicente, Guaruja and Big Beach. Data analysis was based on analytical categories created from the literature that informs this study, reaching two blocks of analysis: one related directly to pharmacies marketing factors, and other factors related to administrative and cost. Data analysis proved to be determinants of mortality micro and small pharmacies in the region, divided in two blocks. In block marketing are related determinants that directly affect the commercial part of the micro and small pharmacies, like the growth of large pharmacy chains, pharmacy program Popular and lack of purchasing power on the part of pharmacies. In the administrative block and costs are related disability in business management, operating costs, taxation and personal problems. Through this research concludes that these factors have weakened the segment of micro and small pharmacies, causing the death of several pharmacies, not sparing even the traditional region of Santos.